2019
DOI: 10.1097/mpg.0000000000002287
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Increased Allocation Priority for Children Awaiting Liver Transplant

Abstract: Objective: The aim of the study was to investigate the impact of prioritizing infants, children, adolescents, and the sickest adults (Status 1) for deceased donor livers. We compared outcomes under two “SharePeds” allocation schema, which prioritize children and Status 1 adults for national sharing and enhanced access to pediatric donors or all donors younger than 35 years, to outcomes under the allocation plan approved by the Organ Procurement and Transplant Network in December 2017 (Organ Procure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…In children, prioritizing the allocation of pediatric grafts to pediatric recipients on the national level prior to adults on the regional level would likely result in decreased mortality in pediatric liver candidates, particularly in the age group <12 years old who have the most difficult time finding appropriately sized grafts. ( 68,70,82 ) One study simulating the effect of the newly implemented acuity circles allocation scheme found that the new UNOS policy will likely decrease waitlist deaths in pediatric recipients and result in more pediatric grafts being allocated to pediatric recipients rather than adult recipients. ( 69 ) In the adult literature, age matching and age mapping are 2 of the more well‐studied equity principles, both of which match organ recipients to donors of a similar age with the theory that younger (and thus better) organs should be prioritized to younger recipients.…”
Section: Age Disparitiesmentioning
confidence: 99%
“…In children, prioritizing the allocation of pediatric grafts to pediatric recipients on the national level prior to adults on the regional level would likely result in decreased mortality in pediatric liver candidates, particularly in the age group <12 years old who have the most difficult time finding appropriately sized grafts. ( 68,70,82 ) One study simulating the effect of the newly implemented acuity circles allocation scheme found that the new UNOS policy will likely decrease waitlist deaths in pediatric recipients and result in more pediatric grafts being allocated to pediatric recipients rather than adult recipients. ( 69 ) In the adult literature, age matching and age mapping are 2 of the more well‐studied equity principles, both of which match organ recipients to donors of a similar age with the theory that younger (and thus better) organs should be prioritized to younger recipients.…”
Section: Age Disparitiesmentioning
confidence: 99%
“…No hubo diferencias significativas en la mediana de puntaje MELD/ PELD al alistamiento en cada grupo (p = 0,136) (Tabla 1). La mediana de puntaje MELD/PELD al alistamiento fue menor en pacientes con etiología colestásica comparado con otras etiologías (17 [9][10][11][12][13][14][15][16][17][18][19][20][21] versus 21 [20-30], respectivamente; p = 0,003). Debido a falta de registro del puntaje MELD/PELD al retiro de LE (por trasplante o fallecimiento), no se consideró esta variable en el análisis.…”
Section: Resultsunclassified
“…De hecho, aquellos pacientes que fallecieron lo hicieron precozmente, ya que la mitad de los pacientes pediátricos fallecen antes de cumplir 3 meses en LE. Por ende, la implementación del sistema MELD/PELD en Chile no ha disminuido desde la era previa a MELD/PELD (25%-29%), lo cual aún está por encima de cifras latinoamericanas de mortalidad pediátrica en LE (Argentina 18% y Brasil 15%) o norteamericanas (10%) 7,13,14 . Sin duda, esto genera una gran cantidad de años de vida potencialmente perdidos en nuestros candidatos.…”
Section: Discussionunclassified
“…The feasibility of a decrease in pediatric wait list deaths, concurrent with an overall increase in LTs performed, was recently demonstrated in a liver simulated allocation model analysis prioritizing pediatric plus the sickest (Status 1) adult patients for deceased donor livers utilizing data from the SRTR. 21…”
Section: Allocationmentioning
confidence: 99%
“…Despite 5%‐10% yearly increases in organ donation and concurrent increments in total transplants performed annually, death or “removal for too sick to transplant” rates range from 7% to 12% on the pediatric LT wait list, while the number of pediatric LTs performed yearly has remained relatively fixed. The feasibility of a decrease in pediatric wait list deaths, concurrent with an overall increase in LTs performed, was recently demonstrated in a liver simulated allocation model analysis prioritizing pediatric plus the sickest (Status 1) adult patients for deceased donor livers utilizing data from the SRTR …”
Section: Introductionmentioning
confidence: 99%